(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): Which are the building blocks of the organizational resilience model that contribute to the successful management of changes in the organizational environment? Purpose: The purpose of the research is a review of domestic and foreign professional literature, where the authors investigate organizational resilience and its models for successful adaptation and response to changes in the ecosystem of the organization. Method: The method is based on a review of domestic and foreign professional and scientific literature, where we focused on open-type articles and doctoral dissertations in the period 2020-2024. The search was performed in the Cobiss, ProQuest Dissertations & Theses, Scopus, ScienceDirect, Web of Science and SpringerLink databases and the FOŠ repository. The search terms were "resilience", "organization", "resilience model", "change management" and "leadership". Results: By the literature review, we found that there is no specific model of organizational resilience that can be measured. We have identified the building blocks of the model, which are based on the principles of organizational resilience, as given by the international standard ISO 22316:2017. The findings will be the basis for further research and study of how these building blocks are recognized in companies and how they can help to facilitate and better manage changes. Organization: Organizations are oriented towards the achievement of goals arising from the company’s strategy. At the same time, they are faced with a constantly changing environment in which they operate and the influences that they must take into account in their performance. In achieving these goals and successfully responding to changes, the resilience model can help them by understanding and taking into account the building blocks of this model. Society: The broader social impact of the research is greater resilience of organizations and awareness of the influences on its resilience. Originality: The literature review showed that the field of organizational resilience research in Slovenia is poorly covered. The research represents a contribution to the understanding, which building blocks are important for organizations to successfully respond and adapt to changes. Limitations / further research: The limitation of the research is a small sample of domestic professional and scientific literature and the lack of research among Slovenian (small and medium-sized) companies. The proposal for further research goes in the direction of collecting data and information from Slovenian companies regarding their resilience and success in responding to changes in their environment.